MAKNA ZAUJ DALAM TAFSIR KEMENTERIAN AGAMA REPUBLIK INDONESIA (ANALISIS STRUKTURALISME LINGUISTIK) - Laela Alfiyah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
The phenomenon of late pairing is rife in Indonesia. Starting from couple trends on social media, household problems in the film Berkalung Sorban Women, to the number of increase in domestic violence rates in Indonesia. The Qur'an mentions the word zauj in 68 verses, spread in 43 suras, with different words. This study aims to examine more deeply the word zauj in the Qur'an which is translated and interpreted by the Ministry of Religion of the Republic of Indonesia, and provides a useful description of the analysis of linguistic structuralism in the translation and interpretation of verses containing the word zauj.